Ways to improve control of excise tax administration in the Republic of Uzbekistan (Eurasian Research Bulletin, 2024)
The article states that excise taxes are included in the price of excise goods and thus passed on to final consumers. At the same time, the amount of excise tax significantly determines the price level of taxed goods, and also affects consumer demand. Excise tax plays an important role in the formation of state revenues and regulation of consumption of certain goods and services. This article reviews the existing literature on excise tax administration, draws conclusions from international best practices. It defines the main directions of improvement of control mechanisms, the main focus is on policy reforms, technological integration and capacity building in tax authorities